Manufacturing of wollastonite-based glass from cement dust: Physical and mechanical properties. Issue 1 (31st December 2016) - Francis, A.A.; Abdel Rahman, M.K.
Abstract: By-pass cement dust is considered as a source of environmental pollution. Wollastonite-based glass foams are made by adding glass waste and SiC to the cement dust. XRD on samples indicated that the main crystalline phase after heat treatment at 850–1, 000°C is wollastonite. Empirical models were developed to derive conclusion on the impact of SiC and temperature on the physical and mechanical properties of the products. The optimum sintering temperature was found to be at 900°C for 60 min, at which crushing strength was about 15 MPa and was the best uniform. Such wollastonite-based glass foam could be very attractive for thermal and acoustic applications.